The Effectiveness of 2D Animation Videos on Disaster Mitigation: Students Elementary Schools' Knowledge of Flood Preparedness - Berliana, Alfina Putri; Wijayanto, Pradika Adi (Education and Talent Development Center Indonesia (ETDC Indonesia), 2025)
This study examines the effectiveness of 2D animation media on students' knowledge of flood disaster mitigation. The research design is a quasi-experimental study. The study population consists of 64 fifth-grade students at several public elementary schools in Daleman. The sampling technique used was total sampling. Class V-A of Daleman State Elementary School served as the control class, while Class V-B served as the experimental class. Data collection techniques included tests (pre-test and post-test) and non-test techniques such as observation, interviews, and documentation. Initial data analysis techniques included normality tests, while final data analysis involved t-tests and N-Gain. The research results indicate that there is a significant difference between the learning outcomes of students in the experimental class and the control class. The findings of the study indicated that the t-test results, a significance value of sig. = 0.000 (sig. < 0.05), were obtained, thus rejecting H₀ and accepting Hₐ. This indicates that 2D animation media has a significant effect on improving students' knowledge of flood disaster preparedness. The N-Gain analysis results support these findings, with an average increase in learning outcomes in the experimental class of 0.6047 (moderate category), while the control class only reached 0.3034 (low category). These findings confirm that 2D animated video media can create a more meaningful learning experience and significantly improve students' conceptual understanding. This study suggests that technology-based learning innovations should be utilised more widely to improve learning quality, particularly in instruction on disaster mitigation for elementary schools.